Intellectual Capital as A Competitive Advantage Source for Businesses - Irma Setyawati (International Journal of Artificial Intelligence Research, 2022)
Intellectual capital has been identified as the fundamental source of wealth creation and firm sustainability. This is accomplished through the application of what individuals currently know as well as the invention of new information, which is a source of organizational competitive advantage. The accumulation of new information is the means by which this goal can be achieved. In this piece of work, an attempt is made to study the role of intellectual capital as a source of competitive advantage by conducting a theoretical-conceptual evaluation of a significant amount of vocabulary. This evaluation is carried out in order to study the role of intellectual capital as a source of competitive advantage. The key insights that have been gleaned from the research that has been conducted up to this point and that has been published point to the significance of intangible assets in the process of cultivating a sustainable competitive advantage for a company. An investigation of the components that contribute to intellectual capital as a possible source of competitive advantage is the primary contribution that this study makes.